Modelling the cost effectiveness of rapid point of care diagnostic tests for the control of HIV and other sexually transmitted infections among female sex workers. Issue 5 (29th September 2006) - Vickerman, P; Watts, C; Peeling, R W; Mabey, D; Alary, M
Abstract : Background: In sub-Saharan Africa, gonococcal and chlamydial infections are usually managed using the syndromic approach. However, many infections are asymptomatic in women, and the syndromic algorithm has poor sensitivity and specificity for infections caused by Neisseria gonorrhoeae (Ng) and Chlamydia trachomatis (Ct). Because of this, rapid point of care (POC) tests for Ct/Ng could improve sexually transmitted infection (STI) management in women. This study uses mathematical modelling to estimate the incremental cost effectiveness of using POC tests to diagnose Ng/Ct instead of the current syndromic approach used by the SIDA2 HIV/STI prevention project for female sex workers in Cotonou, Benin. Methods: A dynamic mathematical model was used with data from Cotonou to estimate the HIV impact of the existing SIDA2 project (1995–8), and to project how impact would change if POC tests had been used. As observed in test evaluations, the POC tests were assumed to have high specificity, but a range of sensitivities. The incremental economic cost effectiveness of using POC tests was modelled using data on intervention costs and an evaluation of an Ng POC test in Cotonou in 2004. All costs were in 2004 US. Results: The model estimated the STI treatment aspect of the intervention averted 18 553 Ng/Ct and 359 HIV infections over 4 years when the syndromic approach was used. In contrast, if Ng/Ct had been diagnosed with a 70–80% sensitive and 95% specific POC test then 24–31% fewer clinic attenders would have been treated, 40–60% more Ng/Ct and HIV infections would have been averted, and the incremental cost effectiveness of using them would have been 107–151 per HIV infection averted if the POC tests cost 2 and 58–81 if they cost 1. Conclusions: POC tests can be a cost effective strategy for substantially increasing the impact on HIV transmission, and decreasing the degree of inappropriate treatment of STI treatment interventions that use syndromic management to diagnose Ng/Ct.